Distributed control and monitoring based on cooperating agents: an application for manufacturing system, ISSN / e-ISSN 2170-161X / 2488-2082 - Chouhal Ouahiba; Mahdaoui Rafik; Mouss Leila Hayet (Journal of New Technology and Materials, 2019)
Control and monitoring of current manufacturing systems has become increasingly a complex problem. To expand their reliability we propose in this work a distributed approach for control and monitoring using the Multi Agents Systems. This approach is based on the decomposition of the complex system into subsystems easier to manage, and the design of several agents each one on these agents is dedicated to a particular task. A software application supporting this approach is developed for the cement clinker system of the Ain Touta cement plant. It is chosen to test the approach on real data. The results show that our distributed approach produces better results than the centralized health monitoring and control.